2020
DOI: 10.1016/j.jcmgh.2020.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of TFEB-Mediated Lysosomal Biogenesis in Alcohol-Induced Pancreatitis in Mice and Humans

Abstract: Chronic plus binge alcohol impaired transcription factor EBmediated lysosomal biogenesis in the mouse pancreas, resulting in insufficient autophagy and pancreatitis. Genetic deletion or overexpression of transcription factor EB in the mouse pancreas exacerbated or protected against alcoholinduced pancreatic damage. BACKGROUND & AIMS: Alcohol abuse is the major cause of experimental and human pancreatitis but the molecular mechanisms remain largely unknown. We investigated the role of transcription factor EB (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 45 publications
(64 reference statements)
0
33
0
Order By: Relevance
“…The protein levels of autophagy related 7 (ATG7) and LC3-phosphatidylethanolamine conjugate (LC3-II), 2 widely used autophagy markers, were consistently and notably up-regulated under S100A11 overexpression both in vivo ( Figure 8 C and D ) and in vitro ( Figure 8 F and G ). Another autophagic protein, the widely used P62, 48 was decreased significantly in the S100A11 overexpression Hepa 1–6 cells ( Figure 8 I and J ) and Hep 3B cells ( Figure 9 A and B ), indicating an activated autophagic status. Similarly, the mRNA levels of some of the autophagic genes, such as Atg5 and Atg7 , were slightly but significantly increased in the CON + S100A11 group compared with the CON + GFP group ( Figure 9 C–E ).…”
Section: Resultsmentioning
confidence: 94%
“…The protein levels of autophagy related 7 (ATG7) and LC3-phosphatidylethanolamine conjugate (LC3-II), 2 widely used autophagy markers, were consistently and notably up-regulated under S100A11 overexpression both in vivo ( Figure 8 C and D ) and in vitro ( Figure 8 F and G ). Another autophagic protein, the widely used P62, 48 was decreased significantly in the S100A11 overexpression Hepa 1–6 cells ( Figure 8 I and J ) and Hep 3B cells ( Figure 9 A and B ), indicating an activated autophagic status. Similarly, the mRNA levels of some of the autophagic genes, such as Atg5 and Atg7 , were slightly but significantly increased in the CON + S100A11 group compared with the CON + GFP group ( Figure 9 C–E ).…”
Section: Resultsmentioning
confidence: 94%
“…53 There are recent reports of TFEB in lysosomal biogenesis during pancreatitis. 54,55 Further work is required to investigate the role of calcineurin substrates in transducing calcium-calcineurin signals during pancreatic acinar cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous groups demonstrated a role for both TFEB and TFE3 in the regulation of lipid metabolism and energy homeostasis in the liver, where TFEB and TFE3 overexpression was sufficient to reverse weight gain and metabolic syndrome in diet-induced and genetic models of obesity, while TFEB/TFE3 deficiency aggravated the phenotype [39,65]. TFEB overexpression also protected from liver damage in alcohol-induced pancreatitis and alcoholic steatohepatitis mouse models [66,67]. We have previously shown that loss of FLCN in C. elegans and mammalian cells increased innate immune response in a process dependent on TFEB and TFE3 [43].…”
Section: Discussionmentioning
confidence: 99%